Capturing Antibiotic Resistance Genes in the Human Gut Microbiome After Probiotic and Antibiotic Exposures - Guitor, Allison Kate (My University, 2023)
Antibiotic-resistant bacteria and their often-untreatable infections are increasing globally. The determinants that confer reduced susceptibility to antibiotics are encoded in the genetic information, or genes, of bacteria. Sequencing-based approaches to identify antibiotic resistance genes (ARGs) in diverse environments, such as the gut microbiome, are limited in throughput and inaccessible due to high costs. The microbiome and its associated ARGs are shaped by many factors throughout early life, which have yet to be fully characterized. In this thesis, I developed an approach to capture ARGs in the gut microbiome and study the effect of various early-life exposures. First, I describe a set of over 37,000 probes to target over 2,000 ARGs. This targeted sequencing approach was designed and validated against samples of DNA isolated from multi-drug resistant bacteria. This probeset proved superior to metagenomic shotgun sequencing in capturing the rare portion of ARGs from a human gut microbiome sample. Second, I investigated the potential benefits of providing probiotics to infants born preterm in reducing antibiotic resistance in their gut microbiomes. Preterm infants that received probiotics had a reduced burden of ARGs associated with potentially pathogenic bacteria at 5 months of age compared to non-probiotic-supplemented preterm infants. Finally, I explored the potential consequences of macrolide antibiotic exposure on ARGs in the gut microbiome of children with diarrhoea in Botswana, Africa. Compared to the standard treatment for diarrhoea, a three-day dose of azithromycin did not result in an increased selection for ARGs after 60 days. This thesis tackles the challenge of comprehensively detecting antibiotic resistance in the gut microbiome. A better understanding of the impact of early-life exposures, including probiotic and antibiotic treatments, in the prevention or maintenance of ARGs in the gut microbiome of children will help reduce unnecessary selective pressures and the persistence of antibiotic resistance into later life.
FACTORS IMPACTING ANTIBIOTIC RESISTANCE IN THE MICROBIOME
Keywords: Antibiotic resistance; Microbiome; Probiotics; Preterm infants; Antibiotics; Next-generation sequencing